LAW REFORMS ARE FOR THE BENEFIT OF PEOPLE! - Zokirov Shohruxbek Zohidjon o‘g‘li (Scholar Express Journals, 2023)
The article contains proposals regarding the law reforms being carried out in the Republic of Uzbekistan, areas requiring law reforms, a number of problems and shortcomings.
Keywords: Republic of Uzbekistan; Law reforms; lawyer; doctors